2015
DOI: 10.1007/s00382-015-2516-2
|View full text |Cite
|
Sign up to set email alerts
|

On the response of Indian summer monsoon to aerosol forcing in CMIP5 model simulations

Abstract: The Indo-Gangetic plains (IGP), which hosts 1/7th of the world population, has undergone significant anomalous changes in hydrological cycle in recent decades. In present study, the role of aerosols in the precipitation changes over IGP region is investigated using Coupled Model Inter-comparison Project-5 (CMIP5) experiments with adequate representation of aerosols in state-of-the art climate models. The climatological sea surface temperature experiments are used to explore the relative impact of the aerosols.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…More specifically, for the model response in temperature at 200 hPa, the results reproduce the upper tropospheric warming over the ocean, but do not replicate the cooling over the Indo-Tibetan landmass. This is possibly because of the role of other processes on the upper tropospheric temperatures, such as aerosol forcing 39,40 and stratosphere-troposphere interactions 41 , which are not included in the model experiment. It may also be noted that previous studies 41 have suggested that the NCEP upper tropospheric data overestimate the cooling trend over the Indo-Tibetan landmass.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…More specifically, for the model response in temperature at 200 hPa, the results reproduce the upper tropospheric warming over the ocean, but do not replicate the cooling over the Indo-Tibetan landmass. This is possibly because of the role of other processes on the upper tropospheric temperatures, such as aerosol forcing 39,40 and stratosphere-troposphere interactions 41 , which are not included in the model experiment. It may also be noted that previous studies 41 have suggested that the NCEP upper tropospheric data overestimate the cooling trend over the Indo-Tibetan landmass.…”
Section: Resultsmentioning
confidence: 99%
“…The Indian Ocean and monsoon exhibit a coupled relationship 32,42,43 , and it is also possible that a feedback from a weak monsoon accelerates the warming in the Indian Ocean 22 . Some studies have suggested a role for anthropogenic aerosols in weakening the monsoon circulation during the recent decades 40,[44][45][46][47][48] . It is possible that such a weakened circulation amplifies the SST warming due to a decreased evaporation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations